PENGARUH KETERLIBATAN TERHADAP NIAT REKOMENDASI YANG DIMEDIASI OLEH PENGALAMAN DAN KEPUASAN BERWISATA PADA PENGUNJUNG MUSEUM TSUNAMI ACEH - Fachrur Razi Dudona; Abdul Rahman Lubis (Departemen Manajemen, 2022)
This study aims to measure the effect of engagement on recommendation intentions mediated by experience and satisfaction with visitors to the Aceh Tsunami Museum. The sample used in this study was 96 visitors to the Aceh Tsunami Museum. Data collection equipment used in this study was a questionnaire. The sampling technique used is convenience sampling. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involvedBased on the results of the HLM, indicating that involvement has a positive effect on recommendation intention, involvement has a positive effect on experience, involvement has a positive effect on satisfaction, experience has a positive effect on recommendation intention, satisfaction has a positive effect on recommendation intention, involvement has an effect on recommendation intentions mediated by experience and satisfaction .